2013
DOI: 10.1111/nuf.12024
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Manager Succession Planning: A Concept Analysis

Abstract: Health care has failed to strategically plan for future leadership. Developing a strong nursing leadership pipeline requires deliberate and strategic succession planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 25 publications
3
58
0
3
Order By: Relevance
“…Our findings also show that NMs who use different knowhow in nursing management, based on evidence or best practices, bring a sense of motivation and achievement to the workplace. [65][66][67][68][69][70] In this regard, our results are in line with those reported by Mackoff, Glassman, and Budin [66] in their qualitative participatory action study with 43 NMs that examined the development of a learning laboratory based on knowledge and experiences. Their results indicated that a learning culture within the healthcare organization offered learning activities addressing the needs of NMs.…”
Section: 4supporting
confidence: 82%
See 1 more Smart Citation
“…Our findings also show that NMs who use different knowhow in nursing management, based on evidence or best practices, bring a sense of motivation and achievement to the workplace. [65][66][67][68][69][70] In this regard, our results are in line with those reported by Mackoff, Glassman, and Budin [66] in their qualitative participatory action study with 43 NMs that examined the development of a learning laboratory based on knowledge and experiences. Their results indicated that a learning culture within the healthcare organization offered learning activities addressing the needs of NMs.…”
Section: 4supporting
confidence: 82%
“…It is clear, also, that such support is essential to their wellbeing at work and to employee attraction and retention in this field of management. The results of our study corroborate the empirical work of Benner, [44] Shermont, Krepcio, and Murphy, [67] Titzer and Shirey, [68] showing that activities (orientation program, personalized coaching, and structured mentorship) facilitate the integration of novice NMs. These activities remain a prerequisite for role transition and enhance novice's attraction and retention.…”
Section: Personalized Support Addressing the Specific Needs Of Novicesupporting
confidence: 81%
“…Nurse managers (NMs) play an integral role in building and sustaining workplaces conducive to improved productivity, cost, quality and timely delivery of health care services (Johnson, Smith, & Mastro, ; Titzer & Shirey, ). Within this context, a host of health care trends co‐exist in Canada, such as rapidly intensifying costs, inefficiencies, lack of consumer‐centeredness and concerns about the overall quality and safety of health care (Fine, Golden, Hannam, & Morra, ; Steed, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nurse managers need to be educated and knowledgeable on health care reform including the Patient Protection and Affordable Care Act, oversee multimillion dollar budgets, leverage technology, and champion performance improvement (PI). [4][5][6][7][8] Nurse manager turnover and vacancies are of increasing concern as managers are promoted, retire, move away, or step down because of the demands of the position and because of strong resistance by staff nurses to assume management positions. 1 With the increasingly complex and dynamic health care landscape, it is no longer prudent for a novice NM to assume the role with minimal preparation and untested leadership skills.…”
mentioning
confidence: 99%
“…The Institute of Medicine's landmark report on the Future of Nursing recommended that we must ''prepare and enable nurses to lead change to advance health care,'' so that nurses can position themselves to lead decision making across all venues, including public, private, and governmental health care agencies. 6,8 In a 2006 workforce survey by the Bernard Hoges Group, 55% of the nurses stating their intention of retiring between 2011 and 2020 were NMs. Highly performing nursing departments and health care organizations require competent, engaged, and resourceful leaders, ready to manage and lead the next generation in this time of transformational change.…”
mentioning
confidence: 99%